2017
DOI: 10.12693/aphyspola.132.577
|View full text |Cite
|
Sign up to set email alerts
|

A Model Proposal for Wall Material Selection Decisions by Using Analytic Hierarchy Process (AHP)

Abstract: Analytical hierarchy process, developed by Saaty, is a multi-criteria decision making method. It creates a hierarchy using the goal, decision criteria and decision alternatives, and sorts the various alternatives according to their relative importance. The aim in AHP is to choose the most suitable and important alternative, by making an arrangement from the most important to the least. In this study, a real life material selection application in a hotel building is described by using AHP method. Wall materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With that, the alternatives are sorted according to their relative importance, from the most important to the least. 45 Hambali et al. 43 demonstrated that a material suggested by AHP shares a similar agreement with six different scenarios of sensitivity analysis.…”
Section: Background and Overviewmentioning
confidence: 82%
“…With that, the alternatives are sorted according to their relative importance, from the most important to the least. 45 Hambali et al. 43 demonstrated that a material suggested by AHP shares a similar agreement with six different scenarios of sensitivity analysis.…”
Section: Background and Overviewmentioning
confidence: 82%
“…AHP which presents a useful methodology for MCDM deals with problem in a hierarchical structure (Wang and Chin, 2011). Generally, 1-9 scale proposed by Saaty for establish pairwise comparison matrices are used in AHP method (Ugur and Baykan, 2017). However, crisp values are insufficient to express human thinking and judgment which constitute input for problem.…”
Section: Fuzzy Ahp Methodsmentioning
confidence: 99%
“…Ugur et al declared that material selection is important in many organizations. For the successfulness of an organization, appropriate materials shall be considered in the design and product development for the competitiveness of the manufacturing organization [21]. Te selection of sustainable material has many advantages.…”
Section: Literature Reviewmentioning
confidence: 99%